Pressure induced mechanical, elastic, and optoelectronic characteristics of Cd0.75Zn0.25Se alloy - Iqbal, Muhammad Aamir; Javeed, Saher; Bakhsh, Sunila; Arellano-Ramírez, Iván D.; Khalid, Muhammad; Morsy, Kareem; Shati, Ali A.; Choi, Jeong Ryeol (Frontiers in Chemistry, 2024)
The change in composition and pressure, both of which lead to new desired properties by altering the structure, is particularly important for improving device performance. Given this, we focused here on the mechanical, elastic, and optoelectronic characteristics of the Cd0.75Zn0.25Se alloy using density functional theory at various pressures from 0 GPa to 20 GPa. It is found that the bulk modulus of the material rises with increasing pressure and exhibits mechanical stability as well as cubic symmetry. In addition, the increased pressure leads to a rise in the direct bandgap energy of the material from 2.03 eV to 2.48 eV. The absorption coefficient of the alloy also increases as the pressure increases, where the effective range of absorption covers the broad spectrum of light in the visible range from orange to cyan. This is due to the electronic transitions caused by the altered pressure. The optical parameters, including optical conductivity, extinction coefficient, reflection, and refractive index, are also analyzed under the influence of pressure. Based on this research, effective applications of the Cd substituted Zn-chalcogenides (CdZnSe) alloys in the fields of optoelectronics and photovoltaics are outlined, especially concerning fabricating solar cells, photonic devices, and pressure sensors for space technology.